2000
DOI: 10.1002/1520-6297(200023)16:4<399::aid-agr2>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between economic value added and the stock market performance of agribusiness firms

Abstract: This article examines the relationship between economic value added (EVA) and the stock market performance of 17 publicly traded companies in the Canadian food processing sector. The research is motivated by the increased popularity of EVA in corporate finance and by the claims that high EVA causes incremental gains in share price values. Using1996 annual reports to compute EVA, and daily stock prices for 1994 through 1998, we attempt to correlate EVA with a variety of measures including accounting return on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 3 publications
3
26
0
5
Order By: Relevance
“…EVA it is an estimate of the amount by which earnings exceed or fall short of the rate of return shareholders and lenders could get by investing in other securities of comparable risk and includes a charge against profit for the cost of all the capital a company employs. Isa and Lo (2001), Stewart (1990), Lehn and Makhija (1996), Uyemura et al (1996), Milunovich and Tsuei (1996), Grant (1996) and Turvey et al (2000) carried out on what might be of superior metrics on evaluating firm performance, i.e. either EVA or conventional measures.…”
Section: Methodssupporting
confidence: 88%
“…EVA it is an estimate of the amount by which earnings exceed or fall short of the rate of return shareholders and lenders could get by investing in other securities of comparable risk and includes a charge against profit for the cost of all the capital a company employs. Isa and Lo (2001), Stewart (1990), Lehn and Makhija (1996), Uyemura et al (1996), Milunovich and Tsuei (1996), Grant (1996) and Turvey et al (2000) carried out on what might be of superior metrics on evaluating firm performance, i.e. either EVA or conventional measures.…”
Section: Methodssupporting
confidence: 88%
“…Goetzmann and Garstka (1999) found that long-term survival of companies may be related to accounting earnings, and more, simple EPS does as well or better than EVA at explaining differences across companies and at predicting future performance. Turvey et al (2000) studied the relationship between EVA and share market returns for a sample of 17 publicly traded food firms in Canada. The key finding was that no relationship could be found between the two.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Turvey et al (2000) employ various measures, including share prices and capital asset pricing model returns, to analyze the relationship between economic value added (EVA) and stock market performance among seventeen Canadian food processing companies. High EVA is not found to be correlated with higher shareholder value.…”
Section: Introductionmentioning
confidence: 90%